Conscientious disengagement and whiteness as a condition of dialogue. Issue 2 (July 2018) - Mott, Carrie; Cockayne, Daniel
This commentary explores some of the threads developed by the editors of Dialogues in Human Geography in light of the recent publication and online conversation surrounding our article, 'Citation Matters'. We examine the precariousness of academic speech, question when it's necessary to conscientiously disengage from dialogue, and posit whiteness as a limit of and condition for dialogue. We frame this around the claim, building further on Mouffe's concept of agonism, that different speech acts, in particular within spheres like the academy, and especially in the absence of a clear foundation for dialogue, can be viewed from a point of view of nonequivalence.